Addressing Priority Animal Diseases in the Americas: Guidance from the 2024 International PROCINORTE Animal Health Workshop - Flores Villalva, Susana (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The results and directions of the PROCINORTE 2024 International Animal Health Workshop held in Mexico City are discussed. This workshop brought together specialists from Canada, the United States and Mexico to discuss priority animal diseases and the importance of international collaboration in animal health and food safety. The focus of the workshop included Bovine Tuberculosis (BT), African Swine Fever (ASF) and Emerging Zoonotic Influenza. The workshop emphasized the interdependence between the health of humans, animals and the environment, promoting the “One Health” approach. It underscored the need for a multidisciplinary team to combat these diseases and invited partners to collaborate with PROCINORTE to advance animal health and technology dialogues in the region.